2021
DOI: 10.1155/2021/6642606
|View full text |Cite
|
Sign up to set email alerts
|

Isoegomaketone from Perilla frutescens (L.) Britt Stimulates MAPK/ERK Pathway in Human Keratinocyte to Promote Skin Wound Healing

Abstract: Skin wound healing is essential for recovery from injury, and delayed or impaired wound healing is a severe therapeutic challenge. Keratinocytes, a major component of the epidermis, play crucial roles in reepithelialization during wound healing including cell proliferation. Recent studies have shown that compounds from natural products have candidates for healing skin injury. Isoegomaketone (IK), isolated from leaves of Perilla frutescens var. crispa (Lamiaceae), has various bioactivities. However, the effect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 42 publications
(32 reference statements)
1
7
0
Order By: Relevance
“…According to Veith et al, reactive free radicals activate the vascular endothelial growth factor during angiogenesis. Furthermore, reactive spices are used for wound sterilization (20)(21)(22). In a study by Isbary et al exploring argon plasma in chronic wound healing, no abnormal side effects were observed in tissues (23) and, similar to our study, visceral tissues were not damaged by helium plasma radiation during histopathological examination.…”
Section: Discussionsupporting
confidence: 88%
“…According to Veith et al, reactive free radicals activate the vascular endothelial growth factor during angiogenesis. Furthermore, reactive spices are used for wound sterilization (20)(21)(22). In a study by Isbary et al exploring argon plasma in chronic wound healing, no abnormal side effects were observed in tissues (23) and, similar to our study, visceral tissues were not damaged by helium plasma radiation during histopathological examination.…”
Section: Discussionsupporting
confidence: 88%
“…The results were supported by the ability of PFP in promoting re-epithelialization in a wound healing assay. Previous papers reported the beneficial effect of P. frutescens on the intestinal epithelial barrier by targeting intestinal permeability [ 53 ], whereas Ye-Ram Kim et al showed the increased proliferation and migration of HaCaT cells treated with isoegomaketone, a phytochemical isolated from P. frutescens leaves [ 54 ]. PFP was not as effective in modulating human fibroblast metabolism as it was in human keratinocytes, and it was devoid of capacity in modulating pro-collagen I and elastin synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…Among the principal activated signaling pathways in wound healing are MAPKs [35,36]. MAPK14 was shown to be specifically activated in diabetic patients [37] and could thus be activated by ES, as ES was shown to promote cell proliferation and migration via the activation of MAPKs [38,39].…”
Section: Discussionmentioning
confidence: 99%